Актуальность применения педагогических идей Антона Макаренко в современных условиях - Volodymyr V. Khmelko; Natalia M. Khmelko (Problemy Wczesnej Edukacji)
Outstanding Ukrainian educator Anton Makarenko created children’s labor colonies, which applied at that time innovative methods of raising children, and passed the severe street school. He trained many individuals who actively participated in the reconstruction of industry and agriculture. The authors of this article share their personal experience of establishing the street children rehabilitation center of the 90s, in which they used methods, which are mainly based on the well-known method of education of Makarenko.